Double‐Network Hydrogels Strongly Bondable to Bones by Spontaneous Osteogenesis Penetration. Issue 31 (17th May 2016) - Nonoyama, Takayuki; Wada, Susumu; Kiyama, Ryuji; Kitamura, Nobuto; Mredha, Md.Tariful Islam; Zhang, Xi; Kurokawa, Takayuki; Nakajima, Tasuku; Takagi, Yasuaki; Yasuda, Kazunori; Gong, Jian Ping
Abstract : On implanting hydroxyapatite‐mineralized tough hydrogel into osteochondral defects of rabbits, osteogenesis spontaneously penetrates into the gel matrix owing to the semi‐permeablility of the hydrogel. The gradient layer (around 40 μm thick) contributes quite strong bonding of the gel to bone. This is the first success in realizing the robust osteointegration of tough hydrogels, and the method is simple and feasible for practical use.